1999
DOI: 10.1063/1.371591
|View full text |Cite
|
Sign up to set email alerts
|

Device physics of single layer organic light-emitting diodes

Abstract: We present experimental and device model results for electron only, hole only, and bipolar organic light-emitting diodes fabricated using a soluble poly ͑p-phenylene vinylene͒ based polymer. Current-voltage (I -V) characteristics were measured for a series of electron only devices in which the polymer thickness was varied. The I -V curves were described using a device model from which the electron mobility parameters were extracted. Similarly, the hole mobility parameters were extracted using a device model de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 23 publications
2
29
0
1
Order By: Relevance
“…5,6 In a recent experimental study, however, it has been demonstrated that hole currents from silver and aluminum into OC 1 C 10 -PPV exhibit a very weak temperature dependence, in spite of the presence of a large injection barrier of 1 eV. 7 This behavior is in contrast with the thermionic emission model which predicts a strong thermal activation, dominated by the large injection barrier.…”
Section: Electro-optical Properties Of a Polymer Light-emitting Diodementioning
confidence: 97%
“…5,6 In a recent experimental study, however, it has been demonstrated that hole currents from silver and aluminum into OC 1 C 10 -PPV exhibit a very weak temperature dependence, in spite of the presence of a large injection barrier of 1 eV. 7 This behavior is in contrast with the thermionic emission model which predicts a strong thermal activation, dominated by the large injection barrier.…”
Section: Electro-optical Properties Of a Polymer Light-emitting Diodementioning
confidence: 97%
“…The current in an organic light-emitting diode (OLED) strongly depends on the charge injection barrier [1][2][3][4][5]. The injection barrier is taken as the energy difference between the workfunction of the electrode and the highest occupied molecular orbital (HOMO) or lowest unoccupied molecular orbital (LUMO) energy of the organic semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…The delay time, i.e., the time lag between applying a rectangular voltage pulse to the device and the first appearance of electroluminescence (EL), is identified as the time until the two leading fronts of injected carriers-holes and electrons-meet in the device. Zone of the most intensive EL is typically a narrow sheet (several nanometers in thickness) in proximity to one of the electrodes because of strong asymmetry of hole and electron mobilities (Crone et al, 1999;Friend et al. 1999).…”
Section: Transient Electroluminescence From Light-emitting Diodesmentioning
confidence: 99%